?-Acetato/?-Aqua Bridged Binuclear Vic-Dioxime Complexes Thermal, Magnetic and Spectral Studies - Duman, Sibel; Sekerci, Memet (Chem Soc Pakistan, 2015)
A new amino vic-dioxime ligand, N,N'-[3,3'-{ethane-1,2-di-yl-bis(oxy) bis(3,1-phenylene)}bis(N'-hydroxy-)2-(hydroxyimino)-acetimidamide] (LH4) was synthesized by reaction of 1,2-bis(m-aminophenoxy)ethane and anti- chloroglyoxime. Then, its Cu(II), Ni(II), Co(III) and Cd(II) complexes were synthesized by the ligand and Cu(AcO)(2)center dot H2O, Ni(AcO)(2)center dot 4H(2)O, Co(AcO)(2)center dot 4H(2)O and Cd(AcO)(2) metal salts, respectively. The ligand and its metal complexes were characterized by elemental analysis, FT-IR, H-1-NMR, UV-vis spectra, magnetic measurements and thermal analysis (TGA-DTA) techniques. All complexes were diamagnetic and binuclear. The Co(II) complex was oxidized to Co(III). While suggested structures of Cu(II) and Ni(II) complexes were found as square-planar, Co(III) and Cd(II) complexes were found as octahedral geometries.
Keywords: Amino (vic)under-bar-dioxime ligand; (anti)under-bar-chloroglyoxime; Thermal analysis